Oviposition and Larval Development of the Indian Meal Moth, Plodia interpunctella, on Different Breakfast Cereals - Liba, Tanner; Aikins, M. Jamie; Phillips, Thomas W. (My University, 2018)
Plodiainterpunctella, the Indian meal moth (IMM), is a common pest of grain products. Adult IMMs lay eggs on a food source and once hatched, the larvae consume the product while leaving behind large amounts of frass and silk [1, 2]. The purpose of this experiment was to identify which kind of grain products are at the highest risk of P. interpunctellainfestation by using the lab-rearing diet as a comparison to two different breakfast cereals of the same brand: a frosted cereal and a regular non-frosted cereal. Two-choice tests determined if moths prefer to lay eggs on and which of the choices would b for the larva to develop. At the end of the experiment, it was observed that adult P. interpunctella preferred to lay their eggs on the frosted cereal diet. The frosted cereal diet also proved to be the better of the two for larval survival and growth. This research suggests that frosted cereals may be preferred by this pest, and that such products need special protection during storage.
Keywords: Fall 2018